Attribution of crime motives biases eyewitnesses' memory and sentencing decisions. Issue 10 (25th November 2016) - Hellmann, Deborah F.; Memon, Amina
ABSTRACT: In court, the basic expectation is that eyewitness accounts are solely based on what the witness saw. Research on post-event influences has shown that this is not always the case and memory distortions are quite common. However, potential effects of an eyewitness' attributions regarding a perpetrator's crime motives have been widely neglected in this domain. In this paper, we present two experiments ( N  = 209) in which eyewitnesses were led to conclude that a perpetrator's motives for a crime were either dispositional or situational. As expected, misinformation consistent with an eyewitness' attribution of crime motives was typically falsely recognised as true whereas inconsistent misinformation was correctly rejected. Furthermore, a dispositional vs. situational attribution of crime motives resulted in more severe (mock) sentencing supporting previous research. The findings are discussed in the context of schema-consistent biases and the effect of attributions about character in a legal setting.